CXXURRENCE OF THE SOFT-SHELLED TURILE, PELOCHELYS BIBRONI (OWEN) IN MARINE ENVIRONMENT - Nair, P N Radhakrishnan; Badrudeen, M (Indian Journal of Fisheries, 2011)
A soft-shdQed turtle, Pelochelys bibroni, was caught in a trawl net operated in Palk Bay off Mandapam on 14th September, 1973. This species was &st recorded by Owen in 1853. Later Gray (1864) r^orted this species from Malacca and Philllppine Islands, Strauch (1890) frcnn Fuchow, China, and recently by Jones (1950) from Papua, New Guinea.